2019
DOI: 10.1117/1.jbo.24.2.020502
|View full text |Cite
|
Sign up to set email alerts
|

Micron resolution, high-fidelity three-dimensional vascular optical imaging phantoms

Abstract: . Microscopic and mesoscale optical imaging techniques allow for three-dimensional (3-D) imaging of biological tissue across millimeter-scale regions, and imaging phantom models are invaluable for system characterization and clinical training. Phantom models that replicate complex 3-D geometries with both structural and molecular contrast, with resolution and lateral dimensions equivalent to those of imaging techniques ( ), have proven elusive. We present a method for fabricating phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…While final cured polyurethane is chemically inert, some of its unreacted ingredients such as isocyanates are toxic 134 . RTV silicone 40,135,[144][145][146][147][148][149][136][137][138][139][140][141][142][143] exhibits similar properties to resin-based materials, but allows greater versatility in phantom design. It is composed of liquid polyorganosiloxanes that crosslink upon addition of a catalyst and is widely available in different hardness shores.…”
Section: Non-water-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…While final cured polyurethane is chemically inert, some of its unreacted ingredients such as isocyanates are toxic 134 . RTV silicone 40,135,[144][145][146][147][148][149][136][137][138][139][140][141][142][143] exhibits similar properties to resin-based materials, but allows greater versatility in phantom design. It is composed of liquid polyorganosiloxanes that crosslink upon addition of a catalyst and is widely available in different hardness shores.…”
Section: Non-water-based Materialsmentioning
confidence: 99%
“…Albumen 44,284 Bovine Serum Albumin (BSA) [285][286][287][288] Melting temperature Formaldehyde 79 TiO2 40,138,139,141,145,147,149,152,289 , Al2O3…”
Section: Thermal Damagementioning
confidence: 99%
“…Compared to our previous work 39 , refractive indices closer to the case of biological tissue have been used and the interferometer setup has been included rigorously according to Maxwell’s equations. With the obtained results, it is possible to explain the structure of experimental tomogram images presented elsewhere 62 .
Figure 4Comparison between tomograms simulated for ( a , b ) perpendicular polarisation and ( c , d ) parallel polarisation for an infinitely long cylindrical scatterer with a = 5 μ m radius. The scatterer, distorted according to the refractive index ratio, is indicated by a black line.
…”
Section: Resultsmentioning
confidence: 66%
“…Previous studies already demonstrated the association between OCT imaging signals and the corresponding atherosclerotic tissues [ 68 , 69 ]: for example, lipid-rich plaques show diffuse borders with signal-poor regions, while fibrous plaques show homogeneous and signal-rich regions, meaning that lipid-rich plaques have higher attenuation and backscattering coefficients than fibrocalcific and fibrous plaques [ 69 ]. For this reason, including adequate structural and molecular sources of contrast into the biomodel is crucial, so the OCT phantoms can accurately mimic realistic pathologic conditions [ 70 ].…”
Section: Applications Of Biomimetic Vascular Models For Atherosclerosismentioning
confidence: 99%